(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In order to improve the effectiveness of treatment, the desire to help the patient get rid of all the diseases that have developed in him inevitably leads to the appointment of many drugs - drugs (medicines) - which, in turn, leads to polypharmacy in the patient. Polypharmacy is a serious problem of the healthcare system, which is clinically manifested by a decrease in the effectiveness of pharmacotherapy and the development of unwanted adverse reactions, as well as a significant increase in healthcare costs. The term "polypragmasia" is often used in the medical literature, but there is no generally accepted definition. For this purpose, the parameters of comparing the morphometric indicators of the liver of white rats in normal condition and under the influence of anti-inflammatory drugs in polypharmacy were studied. The goal of the work was to fill in the data on morphological and morphometric parameters of liver tissue.